Evaluation of airborne gamma-ray spectrometry in contrasting landscapes under tropical conditions - Vilela, Raísa Brito (2021)
The area of this work is located in the south region of Minas Gerais State, which presents a great geological complexity, along with different geomorphological landscapes and soil types, with predominance of the weathered soils. The study area has a reliable and high resolution airborne gamma-ray spectrometry survey throughout its territory performed by the former Economic Development Company of Minas Gerais (CODEMIG) in partnership with CPRM (Brazil Geological Service). Airborne gamma-ray spectroscopy detects the natural gamma radiation in the upper 30 cm of the Earth’s surface. The gamma-ray emitting isotopes used in this passive remote sensing are 40K, 238U and 232Th decay series. These are used to infer K, U and Th concentrations. The integrated use of gamma spectrometric images with digital elevation models has great potential for application in soil sciences and has been widely used for regolith mapping, landscape evolution research, environmental applications and others. In Brazil, the usage applies predominantly to geological mapping and mineral exploration. This master's dissertation aims to open paths for the use of these data in the department of soil science and also to understand the aspects that involve the use of these data in the tropical environment. For this purpose, the dissertation is divided in two parts. The first one presents theorical reference about principles of gamma-ray spectrometry and a compilation of scientific papers published regarding soil science. The second part has a scientific article which aims: I) understand the influence of environmental attributes on the dynamics of %K, eTh and eU contents obtained by airborne sensing in contrasting landscapes of south Minas Gerais; II) understand how pedogenesis changes the radioelements signature in tropical landscapes; III) evaluate the potential of gamma spectrometric images in mapping soil’s parent material for regional studies. To achieve these goals gamma spectrometric responses were compared in landscapes at different geomorphological stages for four distinct lithological groups.